2019
DOI: 10.4062/biomolther.2019.025
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter-Induced Aryl Hydrocarbon Receptor Regulates Autophagy in Keratinocytes

Abstract: Particulate matter (PM), which refers to the mixture of particles present in the air, can have harmful effects. Damage to cells by PM, including disruption of organelles and proteins, can trigger autophagy, and the relationship between autophagy and PM has been well studied. However, the cellular regulators of PM-induced autophagy have not been well characterized, especially in keratinocytes. The Aryl Hydrocarbon Receptor (AhR) is expressed in the epidermis and is activated by PM. In this study, we investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…However, contrasting results also have been published. Jang et al recently reported that exposure to particulate matter (PM) induced autophagy via AhR in HaCaT keratinocytes [36]. This discrepancy might be due to the different ligands used for AhR activation and the different methods used for measuring the autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrasting results also have been published. Jang et al recently reported that exposure to particulate matter (PM) induced autophagy via AhR in HaCaT keratinocytes [36]. This discrepancy might be due to the different ligands used for AhR activation and the different methods used for measuring the autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…CYP enzymes can metabolize PAHs, and the formed metabolites can induce cell damage either by the formation of DNA, protein adducts, or the generation of ROS [195,[204][205][206][207][208]. Indeed, PM upregulates the CYP enzyme mRNA and protein expression in vitro and in vivo [119,128,129,134,135,139,141,167,171,172,178,187]. Other ROS producing enzymes are the members of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) family [209].…”
Section: Pm Triggers Exogenous and Endogenous Ros Formationmentioning
confidence: 99%
“…The highly lipophilic PAHs contained in PM 2.5 are major factors leading to mutagenicity [5] and easily penetrate the skin [6]. The aromatic hydrocarbon receptor (AhR) is activated by PM in the epidermis [7]. Upon activation by PAHs, AhR may increase the production of intracellular reactive oxygen species (ROS) [8].…”
Section: Introductionmentioning
confidence: 99%